The Role of Denial in Vaccine Skeptics and “Anti-vax” Blame: A Psychodynamic Approach - Putois, Olivier; Helms, Julie (Frontiers in Psychology, 2022)
In this paper, we propose to account for the blame addressed to vaccine skeptics and “anti-vax” (VS & AV) by considering their attitude as the result of the psychological mechanism of denial, understood in a psychodynamic manner. To that effect, we draw on a secondary account of our clinical experience in two hospital units (psychiatry and intensive care unit), and on openly available media material. First, we lay out how VS & AV can be understood as the result from fetishist risk denial, a specific psychological transaction with an object by which VS & AV people feel intimately protected; this object is viewed as so powerful that its protection makes the vaccine appear irrelevant. Second, we show how this mechanism can explain the specific content of the blame frequently addressed to VS & AV, who are reproached with being selfish by vaccinated people and caregivers. We contend that, contrary to common belief, they are thus blamed because they force others (and especially caregivers) to compensate their lack of self-protection and preservation, which derives from their exclusive relation to an almighty object. While such a relation accounts for the unwillingness to consider vaccination, it also explains the harshness of the blame voiced by caregivers, who feel helpless in most situations as they cannot effectively force VS & AV to take care of themselves and others.